Determination of oxamniquine in capsules by HPLC - Pierri, E. G.; Almeida, Adelia Emilia de [UNESP]; Gremiao, MPD (Elsevier B.V., 2001)
A sensitive, accurate, reliable and easy method was developed for the quantification of oxamniquine in capsules using high-performance liquid chromatography (HPLC) with UV detection. This technique provided conditions for the separation of the active ingredient from the dosage form by extraction in methanol. Isocratic reversed phase chromatography was performed using methanol, water, and triethanolamine (60:40:0.099, v/v/w) (System C) or methanol, acetonitrile, water and formic acid (40:30:30:0.083, v/v/w) (System D) as mobile phase, a stainless steel column (125 x 4 mm i.d., 5 mum) filled with LiChrospher 100 RP-18 (Merck), column temperature of 28 +/- 2 degreesC and detection at 260 nm. The calibration curves were linear over a wide concentration range (1.0-20.0 mug ml(-1) of oxamniquine) to the Systems C and D with good correlation factor (0.9990 and 0.9982, respectively). The average content obtained were 100.1 +/- 1.5% (System C) and 102.4 +/- 0.8% (System D). The presence of lactose, starch, magnesium stearate and sodium laurylsulphate did not interfere in the results of the analysis. The above findings showed the proposed method to be both simple and added advantage of allowing for fast analysis. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: oxamniquine; high-performance liquid chromatography (HPLC); capsules